A highly-distorted octahedron with a C2v group symmetry inducing an ultra-intense zero phonon line in Mn4+-activated oxyfluoride Na2WO2F4. Issue 40 (18th September 2017) - Hu, Tao; Lin, Hang; Cheng, Yao; Huang, Qingming; Xu, Ju; Gao, Yan; Wang, Jiaomei; Wang, Yuansheng
Abstract : A novel Na2 WO2 F4 :Mn 4+ red-emitting phosphor, exhibiting an ultra-intense zero phonon line at 620 nm, is demonstrated to be promising for LED lightings and displays. Abstract : Owing to the magnetic dipole nature, the zero phonon line (ZPL) of Mn 4+ : 2 E → 4 A2 transition is weak unless Mn 4+ is situated at a site deviating from the centrosymmetric nature. Herein, we report a brand-new oxyfluoride, Na2 WO2 F4 :Mn 4+ (NWOF:Mn 4+ ), which shows unprecedented intense red ZPL at ∼620 nm along with relatively weak vibronic transitions under blue light excitation. This peculiar spectral feature is demonstrated to be originated from the highly distorted octahedral coordination environment in the C 2v group symmetry surrounding Mn 4+ . High-resolution spectroscopic studies at 10 K disclose the fine structured electronic/vibronic transitions of Mn 4+ : 2 E, 2 T1 → 4 A2 and the weak electron–phonon interaction (Huang–Rhys factor S < 1) on the Mn 4+ emissive state. Benefiting from the intense ZPL, an ultra-high color rendering index with Ra = 92.7 and R9 = 90.0 is achieved in the w-LED using YAG:Ce 3+ and NWOF:Mn 4+ as color converters, and a wide color gamut of 107.1% NTSC in the w-LED using CsPbBr3 quantum dots and NWOF:Mn 4+ is obtained. Herein, we first demonstrate that Mn 4+ -activated oxyfluorides have great potential in w-LED lighting and display applications. Our study can also enlighten researchers to design highly distorted octahedral sites for Mn 4+ doping to achieve an ultra-intense ZPL.